1997
DOI: 10.1159/000291833
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Nausea Related to Women’s Obstetric and Personal Histories

Abstract: We report the correlation between total hours of nausea in early pregnancy, as a continuous variable, and various factors in women’s obstetric and personal histories. Positive correlations for increased nausea were found with heavier placentae (p = 0.005), non-smoking status (p = 0.004), women with nausea in previous pregnancies (p = 0.005), and women whose mothers experienced trouble with nausea in their pregnancies (p = 0.001). 17 other factors did not relate to pregnancy nausea at the p < 0.01 level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 10 publications
3
45
1
Order By: Relevance
“…It has been reported that cigarette confers protection against PONV due to presence of an anti-emetic substance in tobacco smoke [28]. A number of epidemiological studies have shown that women who smoke during pregnancy are affected by nausea of pregnancy to a much lesser degree than those who do not [29]. The pharmacological receptors which mediate PONV are known to act at the dopamine (D2), cholinergic, histamine (H1), 5-HT3 and NK1 receptors and if there were an antemetic in cigarette smoke it would have to belong to one of these classes of receptor-blocking drugs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that cigarette confers protection against PONV due to presence of an anti-emetic substance in tobacco smoke [28]. A number of epidemiological studies have shown that women who smoke during pregnancy are affected by nausea of pregnancy to a much lesser degree than those who do not [29]. The pharmacological receptors which mediate PONV are known to act at the dopamine (D2), cholinergic, histamine (H1), 5-HT3 and NK1 receptors and if there were an antemetic in cigarette smoke it would have to belong to one of these classes of receptor-blocking drugs.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of theories regarding its aetiology [25,26], but a change in concentration of steroid hormones is thought to be the most likely cause [27]. A number of epidemiological studies have shown that women who smoke during pregnancy are affected to a much lesser degree than those who do not [28]. It would seem reasonable to conclude that smoking in this group of patients exerts its beneficial effects through similar mechanisms as in the patients whose well-being is improved postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently most research on nausea and vomiting of pregnancy focused on its proximate causes, both hormonal, reviewed by Broussard and Richter 3 and Fessler, 6 and genetic, reviewed by Gadsby et al 7 We analyzed the probable evolutionary significance of nausea and vomiting of pregnancy, focusing on 2 questions: (1) Why should physiological changes in early pregnancy result in nausea and vomiting instead of other conceivable symptoms? (2) Could nausea and vomiting possibly serve a useful function?…”
mentioning
confidence: 99%